2010
DOI: 10.1089/ten.tec.2009.0755
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Monitoring of Lipid Accumulation Over Time in Cultured Adipocytes as Function of Culture Conditions: Toward Controlled Adipose Tissue Engineering

Abstract: Adipose tissue engineering is investigated for native fat substitutes and wound healing model systems. Research and clinical applications of bioartificial fat require a quantitative and objective method to continuously measure adipogenesis in living cultures as opposed to currently used culture-destructive techniques that stain lipid droplet (LD) accumulation. To allow standardization, automatic quantification of LD size is further needed, but currently LD size is measured mostly manually. We developed an imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 55 publications
5
64
0
Order By: Relevance
“…We monitored the lipid production in the cultures using a previously developed, non-destructive image-processing-based method, 20 and compared the adipogenic outcomes across the different levels of sustained tensile strains. Eventually, we could identify a domain of critical strains above which adipogenesis in the statically stretched cultures was significantly accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…We monitored the lipid production in the cultures using a previously developed, non-destructive image-processing-based method, 20 and compared the adipogenic outcomes across the different levels of sustained tensile strains. Eventually, we could identify a domain of critical strains above which adipogenesis in the statically stretched cultures was significantly accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on automated analysis of label-free images 8 identified LDs by applying a brightness threshold as a filter. While this approach is straightforward to implement, we found that the results can be sensitive to slight variations in the brightness and contrast of the acquired image, especially when the image contains a heterogeneous distribution of nonuniformly differentiated cells with a range of LD sizes.…”
Section: Discussionmentioning
confidence: 99%
“…After another 48 h, the second medium was replaced with the adipocyte basal medium. On days 4,8,12, and 16, images were recorded for six randomly selected wells, which were then sacrificed for enzymatic assays of total TG content.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations